Psicosis and suicide risk: who, when and why - J. Gonçalves Cerejeira; I. Santos Carrasco; C. De Andrés Lobo; C. Vallecillo Adame; T. Jiménez Aparicio; G. Guerra Valera; M. Queipo De Llano De La Viuda; A. Gonzaga Ramírez; O. Martin-Santiago (European Psychiatry, 2022)
Introduction Suicide rates in people diagnosed with a psychotic disorder can be up to 50 times higher than in the general population, with the lethality of attempts being significantly higher in this group, compared to people diagnosed with other psychiatric disorders. Furthermore, it is known that being male is associated with more serious suicide attempts and higher rates of completed suicides.